2015
DOI: 10.1124/jpet.114.221150
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Mechanism of Action of Volasertib, a Potent and Selective Inhibitor of Polo-Like Kinases, in Preclinical Models of Acute Myeloid Leukemia

Abstract: Polo-like kinase 1 (Plk1), a member of the Polo-like kinase family of serine/threonine kinases, is a key regulator of multiple steps in mitosis. Here we report on the pharmacological profile of volasertib, a potent and selective Plk inhibitor, in multiple preclinical models of acute myeloid leukemia (AML) including established cell lines, bone marrow samples from AML patients in short-term culture, and subcutaneous as well as disseminated in vivo models in immunedeficient mice. Our results indicate that volase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 31 publications
6
70
0
Order By: Relevance
“…In contrast to rigosertib, volasertib induces oncogenic AKT and ERK signalling and synergizes with AKT or mTOR inhibition in vitro 212 . Volasertib demonstrated impressive anti-tumour activity in xenograft models of neuroblastoma (as monotherapy) 213 , ALL (as monotherapy and in combination with cytarabine or quizartinib) 213, 214 , breast cancer (in combination with fulvestrant) 215 and rhabdomyosarcoma (with vincristine) 216 . A clinical phase II trial compared volasertib in combination with low-dose cytarabine versus cytarabine alone for older patients with AML (TABLE 3).…”
Section: Targeting Of Other Cell Cycle Proteinsmentioning
confidence: 99%
“…In contrast to rigosertib, volasertib induces oncogenic AKT and ERK signalling and synergizes with AKT or mTOR inhibition in vitro 212 . Volasertib demonstrated impressive anti-tumour activity in xenograft models of neuroblastoma (as monotherapy) 213 , ALL (as monotherapy and in combination with cytarabine or quizartinib) 213, 214 , breast cancer (in combination with fulvestrant) 215 and rhabdomyosarcoma (with vincristine) 216 . A clinical phase II trial compared volasertib in combination with low-dose cytarabine versus cytarabine alone for older patients with AML (TABLE 3).…”
Section: Targeting Of Other Cell Cycle Proteinsmentioning
confidence: 99%
“…Volasertib (BI6727) is another promising PLK1 inhibitor. Several preclinical experiments have demonstrated that BI6727 is highly efficacious in inducing tumor regression [116], [132], [133], [134]. As a result, this agent has recently been awarded the “Breakthrough Therapy Status” by the Food and Drug Administration for its significant benefit in treating acute myeloid leukemia patients [135].…”
Section: Plk1 and Human Cancermentioning
confidence: 99%
“…Volasertib has a very low IC50 of 0.87 umol/L and was shown to impede proliferation of acute myeloid leukemia (AML) cell lines (64). Additionally, a study in bladder cancer found that volasertib was a potent inducer of cell death and cell cycle arrest (65).…”
Section: Plk1 As a Drug Targetmentioning
confidence: 99%